EXTRACTION AND PURIFICATION OF BETA-GALACTOSIDASE FROM LOCAL ALMOND AND ITS USE FOR LACTOSE INTOLERANCE TREATMENT - & et al., Al-easawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed, extraction and purification of beta-Galactosidase from local almond(Amygdalus communis) for lactose intolerance treatment. The best one among 10 methods method of the extraction was using sodium phosphate buffer at 0.2 molar. Which was achieves the highest specific activity amounted to 3.66unit/mg protein. Then, partial purification of enzyme was done using five methods. The highest specific activity was obtained using the method of precipitation with ammonium sulphate at 30-70% since the specific activity was 15.85units/mg protein. Which represented the best way to precipitation the enzyme. Three iso enzymes were obtained. One of them was taken for its high specific activity(20.10units/mg protein) and ion exchange chromatography was used and followed by gel filtration technique using sephadex-100 column to increase purification. The specific activity was increased to 21.95units/mg protein. Lactose hydrolysis efficiency test was performed and the purified enzyme showed high efficiency in standard lactose hydrolysis test.